(untitled) (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
This study aims to determine the effect of pulp work activities on fine motor skills of children aged 5-6 years at Bintang Mulia Rimbo Panjang Kindergarten, Kampar Regency. This study uses experimental quantitative research using the quasi-experimental Design method with a Nonequivalent Control Group Design design. The research location of Bintang Mulia Rimbo Panjang Kindergarten, Kampar Regency. The subjects of the study were teachers and children aged 5-6 years, while the object of this study was the effect of pulp work cubic activities on fine motor skills of children aged 5-6 years. The population in this study of all students at Bintang Mulia Kindergarten is 39 children. Meanwhile, the sample of this study is students of group B of Bintang Mulia Kindergarten which consists of two classes, class B Ali (Experimental Class), consisting of 10 boys and 6 girls with a total of 16 children. And class B Umar (control class), consisting of 9 boys and 2 girls with a total of 11 children, using the Purposive Sampling technique. The data collection technique uses observation and documentation. Then the data analysis technique used normality tests, homogeneity tests, and hypothesis tests (t-tests). Based on the results of data analysis from this study, it is evident from the difference in fine motor skills of children aged 5-6 years between the experimental class that uses the pulp work cubit activity and the control class that does not use the pulp cubic activity. From the results of the T-test with a significance value of > or 20,323 > 2,201, so that Ha is accepted and Ho is rejected. So it can be concluded that there is an influence of pulp work activities on fine motor skills of children aged 5-6 years at Bintang Mulia Rimbo Panjang Kindergarten, Kampar Regency